(untitled) (Journal of Intellectual Property Rights (JIPR), 2024)
Non-Fungible Tokens (NFTs) have introduced novel mechanisms to authenticate and trade digital art, fostering a vibrant and dynamic marketplace by leveraging blockchaintechnology. However, the rise of NFTs has also prompted a host of legal and ethical considerations that necessitate careful scrutiny. This research paper provides an in-depth exploration of Non- Fungible Tokens (NFTs) as an emerging form of intellectual property that is transforming the digital art landscape.The paper begins by elucidating the principles behind NFTs and their significance to digital art, elucidating how these tokens redefine traditional notions of ownership. It scrutinizes the role of blockchain technology in protecting digital art and the distinctive advantages it provides, such as transparency and immutability.The paper then delves into the critical legal implications, particularly focusing on copyright issues and the evolving regulatory environment, highlighting the dichotomy between the ownership of NFTs and the copyright of the underlying digital artwork. It conducts a comparative legislative analysis of India, the USA, and the UK, indicating the urgent need for regulatory frameworks that can navigate the global and decentralized nature of NFT transactions. The paper engages with ethical concerns, including environmental impact, economic inequality, and artist attribution, underscoring the necessity for balancing innovation with responsibility.Finally, it provides recommendations for regulatory approaches and discusses future implications, emphasizing the need for clarity, balance, and international cooperation in legislation, alongside the importance of continuous dialogue and research. This paper lays the groundwork for further investigations into the fast-evolving world of NFTs and their wider societal impacts.